Relationship marketing: the gap analysis of Kazzponik Sdn Bhd distribution channels / Nurul Fakhri Mohd - Mohd, Nurul Fakhri (2009)
For many manufacturers and wholesalers, the satisfying of distribution has become preeminent in differentiating the company’s products from those of its competitors. In order to have a business in a good way, the business needs to keep their relation with the distributors to secure a long term relationship. The character and quality of the working relationship between interdependent channel members is influenced by both past and anticipated member performance as well as by the actions (behaviors) of the members towards one another. The gap analysis will able the business to identify what factors that will enhance the commitment of channel members towards the business. Channel satisfaction is undoubtedly a major factor that could lead to greater levels of channel commitment the objective of this study is to identify the gap satisfaction that occur between Kazzponic Sdn Bhd with its distribution channels. The gap that has been identified can then be used by Kazzponic Sdn Bhd. There are five attributes that has been classified in order to find the gap which is price, product quality, profit, payment term and delivery time. The respondents are being selected by using convenience sampling because it is quick and easy accessibility. The respondents are from the Kazzponic Sdn Bhd distribution which is calculated to 30. The data obtained from the questionnaires are being analyzed by using SPSS 14.0. The analysis result shows that 3 of the attributes show a negative sign which mean that they are not satisfied with those attributes received from Kazzponic Sdn Bhd.